La infracción de los derechos y garantías constitucionales y legales de los discapacitados como frágil especial en el Ecuador - Sarango Gualán, Digna Clemencia (2015)
Within every society , it is possible to identify people who are at a disadvantage compared to their peers, for reasons of physical, psychological , mental , intellectual, etc. order. , These groups are recognized as vulnerable or priority . In the matter of Ecuador , the Constitution of the Republic guarantees as focus groups , to children and adolescents, older persons , who suffer from a disability, the catastrophic sick, pregnant women, between other . I mean that my work is oriented to people with disabilities and have to be incorporated into different jobs in all public and private institutions as determined by the Constitution of the Republic. Throughout my thesis work and development and demonstrate working code , not satisfied with what determines the constitution of the republic, with handicapped children in certain private companies incorporate only one or two people to cover that whether they are complying with the law, in the public equally not satisfied with the percentage determined by law , is therefore to be able to determine that the rights of persons with disabilities is violated to have full opportunity to work , take note that disability rights are guaranteed by the constitution of the Republic as a focus group , this is not true only acts with political projections . the Labour Code , I have observed that has not been sufficiently developed legal regulations to ensure the labor force participation of people with disabilities. Rather when the service contract is fulfilled are left outside the institutions , since it is in the vast majority of casual contracts and the law determines that once you have completed one year of casual contracts would not be able to return to contract, then here is the violation of the rights of persons with disabilities , and that they should have another treatment in this sense , because in many situations they are householders In addition to reviewing the Law on Disabilities is observed that has not been developed to efficiently provisions determined on such persons , it should increase new rules so that they act in the best shape for the disabled , for this manifest reason that these people are still a social group , who has many disadvantages and marginalization against the rest of the population. In conclusion shows that this group of priority as determined by the Constitution of the Republic, should be treated in a better way , fulfilling the principles of human rights and fulfilling what determines the law that says that everyone is equal before the law , but this in practice is not, and a long way from this legal and constitutional principle is especially meets people with disabilities in different orders and if they are people who are active and not as many times people are told they are passive and do not represent production , I totally disagree with the last as disabled if they are active agents in the production of a state